Temperature adaptation of soil bacterial communities along an Antarctic climate gradient: predicting responses to climate warming - Rinnan, Riikka; Rousk, Johannes; Yergeau, Etienne; Kowalchuk, George A.; Bååth, Erland (Global Change Biology, 2009)
Soil microorganisms, the central drivers of terrestrial Antarctic ecosystems, are being confronted with increasing temperatures as parts of the continent experience considerable warming. Here we determined short-term temperature dependencies of Antarctic soil bacterial community growth rates, using the leucine incorporation technique, in order to predict future changes in temperature sensitivity of resident soil bacterial communities. Soil samples were collected along a climate gradient consisting of locations on the Antarctic Peninsula ( Anchorage Island, 67 degrees 34'S, 68 degrees 08'W), Signy Island (60 degrees 43'S, 45 degrees 38'W) and the Falkland Islands (51 degrees 76'S 59 degrees 03'W). At each location, experimental plots were subjected to warming by open top chambers (OTCs) and paired with control plots on vegetated and fell-field habitats. The bacterial communities were adapted to the mean annual temperature of their environment, as shown by a significant correlation between the mean annual soil temperature and the minimum temperature for bacterial growth (T-min). Every 1 degrees C rise in soil temperature was estimated to increase T-min by 0.24-0.38 degrees C. The optimum temperature for bacterial growth varied less and did not have as clear a relationship with soil temperature. Temperature sensitivity, indicated by Q(10) values, increased with mean annual soil temperature, suggesting that bacterial communities from colder regions were less temperature sensitive than those from the warmer regions. The OTC warming (generally <1 degrees C temperature increases) over 3 years had no effects on temperature relationship of the soil bacterial community. We estimate that the predicted temperature increase of 2.6 degrees C for the Antarctic Peninsula would increase T-min by 0.6-1 degrees C and Q(10) (0-10 degrees C) by 0.5 units.